IMPACT OF ZEE WORLD SOAP OPERAS ON ROMANTIC EXPECTATIONS AMONG MARRIED WOMEN IN ILORIN, NIGERIA - Ibrahim-Olojoku, Aminat Toyin; Abubakar, Ibrahim Yusuf (African Journal of Social and Behavioural Sciences, 2025)
Soap operas impacted women in both positive and negative ways. The tenacity of soap operas to be creative may enable viewers to emulate certain tenets of the show in their relationships, making them more aware of the authenticity and intentions of their partners. This study investigated the impact of Zee World soap operas on romantic expectations among married women in Ilorin, Nigeria. The study adopted a quantitative method using questionnaires to collect data from respondents in the ancient and new settlements of Ilorin. A total of 444 copies of the questionnaire were distributed using purposive sampling and snowballing sampling designs to reach individual respondents who are married women between the ages of 18 and 65 years, while 400 copies of the questionnaire were valid and analysed. The findings showed that married women in Ilorin are active viewers of Zee World soap operas, as the overwhelming majority of married women in Ilorin (90%) watch Zee World soap operas on an average seven (7) to three (3) days a week. They used to derive positive messages from watching Zee World soap operas, as the majority of respondents (74%) (M=3.3, SD = 0.8) said Zee World soap operas taught them to develop sexually intimate relationships with their partners in order to enjoy romantic relationships. The majority of married women in Ilorin (71%), (M=3.2, SD= 0.7) have a positive perception towards Zee World soap operas, while the overwhelming majority of them (92%), (M=2.6, SD=0.9) said that Zee World soap operas are used to promote realistic romantic expectations. Also, the majority of married women in Ilorin (63%) (M = 3.2, SD = 0.6) agreed that Zee World soap operas have increased their affective expectations in their romantic relationships. The study concluded that exposure to Zee World soap operas and their messages have positively influenced the romantic expectations of married women in Ilorin. The study recommended that more educative and informative women-related messages are necessary to be included in Zee World soap operas in order to promote a healthy and prosperous married life devoid of violence and other abuses.